Effect of biological agents on chlorpyrifos content in soil and bulbs, soil fertility, and shallot (Allium ascalonicum L.) yield - Saputri, Agustin Ayu; Rahayu, Rahayu; Widijanto, Hery; Cahyani, Vita Ratri; Rosariastuti, Retno (Journal of Degraded and Mining Lands Management, 2025)
Continuous pesticide application in shallot (Allium ascalonicum L.) cultivation can reduce soil chemical and biological fertility, potentially leading to the accumulation of pesticide residues. Sustainable agricultural practices are therefore needed to restore soil fertility and improve shallot yield. This study was conducted as a field experiment using a randomized complete block design with a single-factor treatment, namely the type of biological agent: control (BA0), Atlantibacter hermannii (BA1), Pseudomonas sp. (BA2), Indigenous bacterial consortium (BA3), Eco enzyme (BA4), and Biofilm (BA5) from Mount Lawu's western slopes. Each experimental treatment was repeated five times, resulting in a total of 30 units. Statistical analysis was done using analysis of variance (ANOVA), followed by Duncan multiple range test (DMRT) and Pearson correlation. The parameters observed included chlorpyrifos levels, chemical and biological characteristics, and shallot yield. The results of the study indicate that Atlantibacter hermannii (BA1) reduced soil chlorpyrifos content by 64.62% and increased shallot yield by 41.44%. Eco enzyme (BA4) and biofilm (BA5) were the most effective in lowering chlorpyrifos accumulation in bulbs, with reductions of 42.31% and 38.46%, respectively. Regarding soil fertility, BA1 increased available phosphorus by 30.32%, Pseudomonas sp. (BA2) increased available potassium by 12%, and BA4 increased total nitrogen by 18.18%; however, the improvements from BA2 and BA4 were similar to those from BA1. Overall, Atlantibacter hermannii (BA1) and eco enzyme (BA4) emerged as the most promising biological agents for reducing pesticide residues, enhancing soil fertility, and increasing shallot production, highlighting their potential application in sustainable agriculture.